Preparation of Proton-Conducting Solid Electrolyte Membrane Based on Carboxymethyl Chitosan Complexed with Ammonium Acetate - Berghuis, Nila Tanyela; Fridarima, Shanny; Rachmadhanti, Elvira Nur; Sudaryanto, Sudaryanto; Ndruru, Sun Theo Constan Lotebulo (Molekul, 2024)
This research aims to prepare the proton-conducting solid electrolyte membrane based on carboxymethyl chitosan (CMCh) complexed with ammonium acetate (CH3COONH4). The membranes were prepared by using casting solution technique where the various weight percentages of ammonium acetate mixed to CMCh for obtaining optimum condition based on ionic conductivity analysis. Some characterizations were conducted to analysis the functional groups (involving complexation studies), ionic conductivities, mechanical properties, crystallinities, and thermal analysis by using FTIR, EIS, tensile tester, XRD, and TGA. The results showed that the optimum proton conductivity was obtained at the addition of 40% (w/w) CH3COONH4 salt as high as 1.39×10-4 S/cm and a tensile strength of 9.06 MPa. Based on the results, it can be concluded that the optimum condition of the membrane shows good characteristics to be applied as a proton conducting solid electrolyte. Keywords: Ammonium acetate, carboxymethyl chitosan, polymer electrolyte, proton conductivity, proton-conducting membrane